2008
DOI: 10.1128/jb.00844-07
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Functional Expression, and Genetic Organization of Cif, a Phage-Encoded Type III-Secreted Effector from Enteropathogenic and EnterohemorrhagicEscherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) and enterohemorrhagic E. coli (EHEC) inject effector proteins into host cells via a type III secretion system encoded by the locus of enterocyte effacement (LEE). One of these effectors is Cif, encoded outside the LEE by a lambdoid prophage. In this study, we demonstrated that the Cif-encoding prophage of EPEC strain E22 is inducible and produces infectious phage particles. We investigated the distribution and functional expression of Cif in 5,049 E. coli strains of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
2
38
2
Order By: Relevance
“…They belonged to phylogroup B1 and harbored no other CM-encoding gene. Cif is an effector protein of the type 3 secretion system (T3SS) encoded by the locus of enterocyte effacement pathogenicity island, and previous observations of the cif gene were restricted to enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC) strains (36,38). The two cif-positive strains of this study were confirmed as EPEC strains by detection of the eae gene but not of stx genes.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…They belonged to phylogroup B1 and harbored no other CM-encoding gene. Cif is an effector protein of the type 3 secretion system (T3SS) encoded by the locus of enterocyte effacement pathogenicity island, and previous observations of the cif gene were restricted to enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC) strains (36,38). The two cif-positive strains of this study were confirmed as EPEC strains by detection of the eae gene but not of stx genes.…”
Section: Resultssupporting
confidence: 52%
“…Only one of the two cif genes produced a cytopathic effect. Loukiadis et al reported that 66% of cif-positive E. coli strains did not induce a Cif-related phenotype in eukaryotic cells due to frameshift mutations or an insertion sequence in the cif gene (36). However, a nonfunctional T3SS may also explain the absence of a cytopathic effect.…”
Section: Vol 48 2010 Cyclomodulins In Urosepsis Strains Of Eschericmentioning
confidence: 99%
“…The C-terminal part of NleH is 46 % identical to that of the Shigella OspG, which contains the three catalytic motifs involved in the OspG function. EHEC O111 also contains a nleH1-1 homologue (Loukiadis et al, 2008). However, Ruchaud-Sparagano et al (2007) observed that IL-8 secretion by Caco-2 cells was still suppressed when the cells were infected with a CesT-defective mutant that is unable to produce the CesT protein, a chaperone required for NleH translocation.…”
Section: Discussionmentioning
confidence: 99%
“…These OspGs are distantly related (about 30 % identity) to another T3SS effector family (Fig. 1b), which comprises NleH of Citrobacter rodentium (Garcia-Angulo et al, 2008) and NleH1-1 and/or NleH1-2 of EHEC O157 strain Sakai, EHEC O111, rabbit EPEC Thomson et al (2006) strain E22, and human EPEC strain B171-8 (Loukiadis et al, 2008;Tobe et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation